Efektivitas Brain Gym Terhadap Konsentrasi Dan Hasil Belajar Siswa Di SDN Hurip Jaya 02 - Jessica Valeni Setyawan; Ira Kusumawati; Rahayu Maharani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Learning concentration is an important factor influencing the success of the learning process in school-aged children. Low levels of learning concentration can lead to a decline in students’ learning outcomes. One non-pharmacological intervention that can be used to improve learning concentration is brain gym or brain exercise. This study aimed to determine the effectiveness of brain gym on learning concentration and learning outcomes of students at SDN Hurip Jaya 02. Methods: This study employed a quantitative design using a one group pretest–posttest design to assess learning concentration and a cross-sectional approach to evaluate students’ learning outcomes. The study population consisted of all students in grades III, IV, V, and VI at SDN Hurip Jaya 02, with a total sample of 73 students selected using a total sampling technique. Learning concentration was measured using the Grid Concentration Test (GCT), while learning outcomes were assessed based on students’ daily assignment scores. The brain gym intervention was administered for 10–15 minutes per session in accordance with standard operating procedures. Data analysis was conducted using the paired simple t-test to evaluate learning concentration and the chi-square test to examine the relationship between learning concentration and learning outcomes. Results : The results of this study showed a significant improvement in learning concentration after the brain gym intervention, with a Sig. (2-tailed) value of 0.000 (p < 0.05). The chi-square test results also indicated a significant relationship between learning concentration and students’ learning outcomes (p = 0.000). Conclusion : This study concludes that brain gym is effective in improving learning concentration and learning outcomes among elementary school students and can be used as a simple, practical, and non-pharmacological intervention in the school setting.